Evaluation of transcatheter heart valve biomaterials: Computational modeling using bovine and porcine pericardium. (September 2019) - Sulejmani, Fatiesa; Caballero, Andrés; Martin, Caitlin; Pham, Thuy; Sun, Wei
Abstract: Objective: The durability of bioprosthetic heart valve (BHV) devices, commonly made of bovine (BP) and porcine (PP) pericardium tissue, is partly limited by device calcification and tissue degeneration, which has been associated with pathological levels of mechanical stress. This study investigated the impacts of BP and PP tissues with different thicknesses and tissue mechanical properties in BHV applications. Methods: Second Harmonic Generation (SHG) imaging was employed to visualize the collagen fibers on each side of the pericardium. Structural constitutive modeling that incorporates collagen fiber distribution obtained from multiphoton microscopy for each tissue type were derived to characterize the corresponding biaxial mechanical testing data collected in a previous study. The models were verified through finite element (FE) simulations of the biaxial test and implemented in valve closing simulations. Results: Smooth side collagen fibers were found to correlate with the mechanical response. BHVs with adult (ABP) and calf (CBP) BP tissues had lower maximum principal stresses than those with PP and fetal (FBP) BP tissues. Collagen fiber orientation along the circumferential axis resulted in lower maximum principal stresses and more uniform and symmetric stress distributions throughout the valve. Conclusions: The use of PP and FBP tissue resulted in higher peak stresses than ABP and CBP tissues in the given valve design. Additionally, ensuring collagen fiber orientation along the circumferential axis led to lower maximum stresses felt by the valve leaflets, which could also improve BHV durability.